LANGGAR SEBAGAI INSTITUSI PENDIDIKAN KEAGAMAAN ISLAM - Kosim, Mohammad (TADRIS: Jurnal Pendidikan Islam, 2009)
Langgar (prayer house) is the oldest Islamic education institution in Indonesia that has been grown and developed in Islamic communities. It is established earlier than pesantren (Islamic boarding school), conventional school, and madrasah (Islamic school). Langgar has been taking an important role in preparing qur’anic generation, especially junior level, for a long time. In the Indonesian Islamic education cluster, langgar is catagorized as one of non-levelling Islamic educations. It has educational elements that forms langgar’s educational system. The system covers students care, santri (students), materials, method, and evaluation. Nowadays, Langgar has been competing with the similar institution which is considered more modern, such as TK al-Qur’an (Islamic kindergarten studying Qur’an).